1982
DOI: 10.1007/bf01805567
|View full text |Cite
|
Sign up to set email alerts
|

Transport inhibition in the pathology of phenylketonuria and other inherited metabolic diseases

Abstract: Kinetic analysis of the rates of transport of amino acids and of sugars across the blood‐brain barrier shows how severe is the competition which commonly occurs between groups of chemically related substances in the blood plasma for one of a number of shared transport carriers. In view of the possible importance of such competition in causing brain damage in inherited metabolic diseases an example is given of the use of these kinetic data to work out the best way of ensuring an adequate supply of amino acids t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 35 publications
1
15
0
2
Order By: Relevance
“…Thus, the increase of only one (Tyr) or three (VIL) AAs may even accentuate disturbances of neurotransmitter or protein synthesis (42). VIL therapy did not find acceptance in PKU treatment.…”
Section: Figurementioning
confidence: 96%
“…Thus, the increase of only one (Tyr) or three (VIL) AAs may even accentuate disturbances of neurotransmitter or protein synthesis (42). VIL therapy did not find acceptance in PKU treatment.…”
Section: Figurementioning
confidence: 96%
“…The kh for histidine in the lamb and methionine in the sheep were estimated. In the adult rat these have been determined using the initial-rate, steady-state technique to be 500 + 80 ,smol 1`for histidine and 580 + 70 smol 1`for methionine (Pratt, 1982). In our study, half-maximal inhibition was observed at much lower concentrations of phenylalanine, suggesting a species difference in the relative affinities of these amino acids for the large neutral amino acid carrier.…”
Section: Brain Influx Of Amino Acidsmentioning
confidence: 46%
“…In particular, the recognition that the affinity constants of blood-brain barrier amino acid transport are within the range of blood concentrations has led to the suggestion that the inhibition of influx of related amino acids may be a significant factor in the causation of cerebral damage in amino acidopathies such as phenylketonuria (Pratt, 1982). The developing brain is especially susceptible to the deleterious effects of a sustained increased in the circulating concentration of particular amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…This influx is interfered with, especially in infancy, if one or more of the serum amino acid levels are exceptionally high. Pratt (Pratt, 1982) reviewed the evidence to date and predicted that adding tyrosine or leucine, valine and isoleucine only, would be ineffective. Despite this, several studies in rats and humans claimed neurological/psychometric improvement with the administration of the branch chain amino acids -valine, leucine and isoleucine (Jordan, 1985;Vorhees, 1989).…”
Section: Large Neutral Amino Acids (Lnaa)mentioning
confidence: 99%